Introduction of heavy metals contamination in the water and soil: a review on source, toxicity and remediation methods - Wei Xu; Yuan Jin; Gang Zeng (Green Chemistry Letters and Reviews)
Heavy metal contamination in water and soil presents a growing global issue that poses significant risks to environmental integrity and human well-being. Various heavy metals, including arsenic (As), lead (Pb), mercury (Hg), cadmium (Cd), and chromium (Cr), contaminate ecosystems. These metals enter the environment through both natural processes and human activities such as coal mining, leather production, metal processing, agriculture, and industrial waste disposal. With their high toxicity and tendency to accumulate in organisms, heavy metals induce oxidative stress in cells, resulting in organelle damage. This toxicity can lead to genetic mutations and histone alterations. Given the severe effects of heavy metals, urgent actions are required to eliminate them from polluted soil and water. While physicochemical techniques like membrane filtration, precipitation, oxidation, and reduction exist, they have limitations. Hence, there is a pressing need to devise environmentally friendly and cost-efficient approaches for heavy metal removal. This article examines heavy metal contamination in water and soil, its adverse impacts, and the cleanup of heavy metals using eco-friendly methods.